Inequality and Market Power: Evidence from the United States and China - Yumin Hu; Luca Macedoni; Mingzhi (Jimmy) Xu (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Using barcode-level data from the NielsenIQ Homescan Consumer Panel, we study how income inequality affects the prices of identical goods across US counties. We find that higher inequality reduces prices for products with low market shares but increases prices for products with high market shares. With higher inequality, larger firms, which sell more high-market-share goods, tend to raise prices, while smaller firms lower them. We find a similar pattern using Chinese export data across countries. To interpret these findings, we develop a model where a mean-preserving spread in income affects pricing through the convexity of demand and the convexity of the price derivative of demand with respect to income. We derive conditions under which inequality raises the price elasticity for low-market-share products and lowers it for high-market-share products, matching our empirical results.
Keywords: L11; D31; D43; F14; 330; consumer heterogeneity; income inequality; prices; markups